CERPEN LESUNG PIPIT KARYA EKA KURNIAWAN: KONSEPSI KEPERAWANAN SEBAGAI STRATEGI PERLAWANAN - Marsten Lihardo Tarigan; Fiona Djunita Natalia Luhulima; Yulia Putri Paradida (Fakultas Bahasa dan Sastra Indonesia Universitas Jenderal Soedirman, 2023)
One of the conceptions held by society today is virginity. This conception of virginity has become an issue of sexuality, which is often an important discussion in society. Virginity is often regarded as the standard of chastity for a woman. The short story